Animal Vulnerability and its Ethical Implications: An Exploration - Martin, Angela K. (Journal of applied philosophy, 2021)
While human vulnerability has been discussed for some time in the contemporary philosophy and bioethics literature, animal vulnerability has received less attention. In this article, I investigate whether the concept of vulnerability, as it is currently used in bioethics, can be meaningfully extended to animals. Furthermore, I discuss the ethical implications of ascribing vulnerability to animals and I show what vulnerability discourse can add to debates on animal ethics. In a first step, I analyse the conditions of vulnerability ascription. By taking as my basis the definition of vulnerability presented by Martin, Tavaglione and Hurst, I demonstrate that some animals fulfil the conditions of vulnerability ascription. I explore the ethical implications of vulnerability ascriptions in three domains: livestock farming, animal experimentation, and animals living in the wild. I argue that many groups of animals currently qualify as particularly vulnerable and should be afforded special protection so that they receive what they are due. I conclude by outlining the differences between vulnerability and sentience ascriptions: while sentience is a sufficient reason to ascribe moral status to a being, vulnerability draws our attention to those who are more likely to be denied what they are due.